Analisis Pengetahuan dan Ketertarikan Siswa SMP Terkait Colin Maclaurin dan Kontribusinya sebagai Peningkatan Minat Matematika - yulyanti -; Alisya Putri Chania; Hafizatunnisa Hafizatunnisa (JNPM (Jurnal Nasional Pendidikan Matematika), 2024)
Maclaurin was a Scottish-born physicist and mathematician who was a direct descendant of the noble Stewart family through his mother. His contributions in the field of mathematics are still relevant to modern scholarship in this century and continue to be used as a basis for the development of other sciences. One of his famous contributions to mathematics is the Maclaurin series. The author is interested in explaining Maclaurin's figure and analyzing the level of knowledge and interest of junior high school students regarding Colin Maclaurin and his contributions. The research used is qualitative research with a case study method. The research subjects were ten middle school students who were chosen randomly. The instrument used in this research was an open interview. Each student was asked five questions related to their knowledge of Maclaurin and his contributions. The analysis of this research data is thematic. The results of this research obtained four levels of knowledge and interest of junior high school students regarding Colin Maclaurin and his contributions. An explanation of the four levels of knowledge and interest will be explained in detail in this article.